2022
DOI: 10.1097/mph.0000000000002483
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Polymorphisms of the HIF1A Gene are Associated With Sensitivity of Glucocorticoid Treatment in Pediatric ITP Patients

Abstract: Background: Hypoxia-inducible factor-1α (HIF-1α) plays a crucial role in both innate and adaptive immunity. Emerging evidence indicates that HIF-1α is associated with the inflammation and pathologic activities of autoimmune diseases, suggesting that HIF1α may be involved in immune dysregulation in patients with immune thrombocytopenia (ITP). The purpose of this study was to evaluate whether single nucleotide polymorphisms (SNPs) of the HIF1A gene are associated with susceptibility to ITP and its clinical progn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…SNPs in genes encoding immune checkpoint proteins (e.g. CD28, ICOS, PD1, DNAM1) have been associated with disease severity and steroid resistance 25 . However, the relevance of these findings to the development of rITP needs further investigation (reviewed in Ref.…”
Section: Genetics and ‘Syndromic’ Itpmentioning
confidence: 99%
“…SNPs in genes encoding immune checkpoint proteins (e.g. CD28, ICOS, PD1, DNAM1) have been associated with disease severity and steroid resistance 25 . However, the relevance of these findings to the development of rITP needs further investigation (reviewed in Ref.…”
Section: Genetics and ‘Syndromic’ Itpmentioning
confidence: 99%
“…Notably, a flow cytometry analysis of patients with ITP demonstrated a lowered interleukin (IL)-10 to IL-17 ratio in the GCR group (16). Additionally, one study using time-of-flight mass spectrometry (MS) analysis revealed that glucocorticoid-sensitive (GCS) individuals exhibited significantly higher levels of sirtuin 1 and hypoxia-inducible-factor 1A, suggesting a potential link to their favourable response to glucocorticoid therapy (17,18).…”
Section: Introductionmentioning
confidence: 99%